2015
DOI: 10.1177/0022427815616991
|View full text |Cite
|
Sign up to set email alerts
|

Updating Perceptions of (In)Justice

Abstract: Objectives: This study evaluates the malleability of judgments of procedural justice. Drawing upon various literatures, five factors are hypothesized to be related to changes in procedural justice: (1) prior judgments of procedural justice, (2) direct experiences of arrest, (3) vicarious experiences of arrest, (4) individual arrest history, and (5) age. Methods: Using 11 waves of data from the Pathways to Desistance Study (N = 1,354), multilevel models relate within-person covariates including individual, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 68 publications
3
57
1
6
Order By: Relevance
“…But they also acknowledge that the stability in the differences "suggests that inter-individual differences among study participants in their cynicism about the legal system likely were established before their first assessment in this study, perhaps as young as fifteen years of age" (287), and the same could be said about their judgments about legitimacy. Megan Augustyn (2015) examined the same sample over a longer time period, finding a decline in offenders' procedural justice judgments, much as Amie Schuck (2013) did, and also that later judgments were influenced by prior judgments. She also found that, curiously, arrests improved offenders' perceptions of procedural justice, and that the positive effect of an arrest increased as offenders aged.…”
Section: Public Trust Of Police In Contextmentioning
confidence: 87%
“…But they also acknowledge that the stability in the differences "suggests that inter-individual differences among study participants in their cynicism about the legal system likely were established before their first assessment in this study, perhaps as young as fifteen years of age" (287), and the same could be said about their judgments about legitimacy. Megan Augustyn (2015) examined the same sample over a longer time period, finding a decline in offenders' procedural justice judgments, much as Amie Schuck (2013) did, and also that later judgments were influenced by prior judgments. She also found that, curiously, arrests improved offenders' perceptions of procedural justice, and that the positive effect of an arrest increased as offenders aged.…”
Section: Public Trust Of Police In Contextmentioning
confidence: 87%
“…Kaiser and Reisig (), for example, found that individual characteristics such as impulse control, moral disengagement, and emotional regulation were more strongly related to between‐ and within‐individual variation in legal cynicism than to legitimacy. Similarly, some scholars have found a stronger associations between legal cynicism and self‐reported offending compared with measures of police legitimacy (see Augustyn, ; Fagan & Piquero, ; Reisig et al., ; but see Kaiser & Reisig, ; Trinkner et al., ).…”
Section: Legal Attitudinal Developmentmentioning
confidence: 93%
“…In applications of learning theories and legal socialization, scholars have shown that other factors such as the accumulation of experiences also inform views about law enforcement as well as about procedural justice (Brunson and Weitzer, ; Rosenbaum et al., ; Weitzer and Tuch, ). People's views of the police are formed through socialization with family, friends, and the community, but as individuals have new encounters with the police, as well as vicarious experiences, their perceptions are “updated”—“as an individual comes into contact with new information, they update their prior judgement” (Augustyn, : 259). Weitzer () argued that how an individual is treated during contact with a police officer is a micro‐level process and is only one aspect that influences people's perceptions of law enforcement.…”
Section: Theoretical Backgroundmentioning
confidence: 99%